QUALITY GRADING OF WOODEN POLES PRODUCED BY SCOTS PINE (PINUS SYLVESTRIS L.) FORESTS IN WEST RODOPI (N. GREECE) - Koutsianitis, Dimitrios; Voulgaridis, Elias (Innovation in Woodworking Industry and Engineering design, 2017)
Trunks of Scots pine (Pinus sylvestris L.) are widely used for poles in power transmission and telecommunication lines. The objective of this work was to apply visual quality indexes on wooden poles, based on basic wood defects. Poles were characterized according to various defects and geometric characteristics, namely: knots, spiral grain, sweep, taper, rate of growth and dimensions. Poles that did not meet the established minimum requirements of the standards applied by the public power corporation, were rejected. The results showed that from the 82 trees investigated a high percentage (90.2%) met the standards and were suitable as power transmission poles.